Antibiotics Contaminated Irrigation Water: An Overview on Its Impact on Edible Crops and Visible Light Active Titania as Potential Photocatalysts for Irrigation Water Treatment - Jalloul, Ghadeer; Keniar, Imad; Tehrani, Ali; Boyadjian, Cassia (Frontiers in Environmental Science, 2021)
Sub-therapeutic levels of antibiotics (ABs) are given to animals and poultry to promote growth and reduce disease. In agricultural environments, ABs reach croplands via animal manure used as fertilizer and/or ABs-contaminated water used for irrigation. The continuous discharge of ABs into the ecosystem raises growing concerns on the ABs contamination of edible crops. Tetracyclines (TCs) are among the most widely used ABs around the world. In this review, we discuss the contamination of irrigation water with TCs, its impact on edible crops, and the potential risks of crop contamination with TCs on human health. We propose solar-mediated photocatalytic degradation using Titania (TiO2) photocatalyst as a promising method to remove TCs from irrigation water. The photocatalytic activity of TiO2 can be enhanced by chemical modification to expand its activity under visible light irradiation. Herein, we aim for providing literature-based guidance on developing a visible light–active TiO2-based system to degrade TCs and other ABs in water streams. We include a summary of recent advances on this topic based on three main modification methods of Titania: metal/non-metal/mixed doping, composite formation, and heterojunction construction. Among the investigated photocatalysts, Fe2O3-TiO2/Fe-zeolite and the N-doped TiO2/rGO immobilized composite catalysts were found to be very efficient in the degradation of TCs under visible light irradiation (i.e., 98% degradation within 60 min). Most immobilized TiO2 based composite systems exhibited improved performances and hence we highlight these as efficient, cost effective and ecofriendly photocatalysts for the degradation of TCs in irrigation water.